PENGEMBANGAN MEDIA TRAINER PINTU OTOMATIS DENGAN SENSOR ULTRASONIK, RFID, DAN PIR BERBASIS ARDUINO PADA MATA PELAJARAN MIKROPROSESSOR DAN MIKROKONTROLER KELAS X DI SMKN 1 DRIYOREJO - Jenaro, Deva Feggantara Pakshi; Sulistyo, Edy; Santosa, Agus Budi; Widodo, Arif (Universitas Negeri Surabaya, 2021)
This research is based on the results of observations at SMKN 1 Driyorejo and the problem is that there is no trainer as a practicum tool for students. For this reason, there is a need for learning media that can make students learn independtly. This study aims to (1) to know the eligibility of the automatic door sensor trainer in the microprocessor and microcontroller subjects, (2) Get eligibility automatic door sensor worksheets on microprocessor and microcontroller subjects, (3) find out how much students response about automatic door trainers and jobshets given in Microprosessor and Mikcrocontroler subjects at SMKN 1 Driyorejo academic year 2020/2021.The research and development (R&D).By collecting data using validation sheets given to 3 lecturers of the Electrical Engineering Departements of UNESA and 3 teachers of SMKN 1 Driyorejo as validators.This research consists of 7 stages,namely : (1) the ability analysis stage and problems,(2) the data collection stage, (3) the product design stage , (4) the design validation stage, (5) the design revision stage, (6) the product trial stage and , (7) the data analysis and reporting stage. The results showed that the validity of the trainer was 91.96% and the jobsheet was 81.77%. Meanwhile, the average value of the results of student responses to the audio system installation trainer with 2 aspects, namely the trainer convenience aspect and the display and media qualityaspects, the calculation result was 84.14%. With the data obtained, the Arduino-based Automatic Door trainer is suitable for use.